EARLY MARRIAGE AND ITS INFLUENCE ON FAMILY HARMONY IN AN ISLAMIC PERSPECTIVE - M Musthofa; Sarah Qonita Lutfiah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
Early marriage is marriage at a relatively young age and has a complex influence on family harmony. Family harmony is a condition where household happiness is achieved and there is little conflict so that a peaceful and harmonious family is created. In addition to early marriage, among family factors it becomes less harmonious because of a lack of mental and emotional readiness, financial stability, readiness to assume responsibility, and level of education. Also, there is communication within the family that is not smooth and good, lacks mutual respect, does not support each other, and does not understand each other's needs. Thus, early marriage is not the only factor that affects family harmony, but other factors must also be considered to build harmonious and happy relationships in the family. In Islam, harmony in the family is considered very important. The family is considered the foundation of society and important for maintaining the integrity and stability of society. More specifically, the family in Islam is seen as a relationship that is regulated by the provisions of Islamic law. This includes the duties and responsibilities of each family member, rights and obligations, as well as laws that must be obeyed in everyday life. Islam also emphasizes the importance of balance in the family, where husband and wife must support each other and work together to achieve the common goal of building a happy and harmonious family. So the writer tries to raise this phenomenon with the title, "Early marriage and its influence on family harmony in an Islamic perspective". Keywords: early marriage, harmony, family, Islamic perspective.